Entendimentos a respeito da matemática na educação do campo: questões sobre currículo - Barbosa, Linlya Natássia Sachs Camerlengo de [UNESP] (2014)
This thesis is part of the Program Ethnomathematics and its central purpose is to show and to discuss the ways to understand the mathematics curriculum in rural education. For that, I draw panoramic images, based on academic publications, on the courses of Bachelor in Rural Education with specialization in Mathematics and on seven interviews. With that, I compose four images zoomed in, focusing aspects of scholar curriculum, specifically of mathematics, in rural education. The first one considers that the mathematics contents to be taught in rural schools should be the same as any other school, but it's important to start from the student's reality; the second one, on the contrary, questions the knowledge that composes the programs and it suggests including local knowledge, which historically has been excluded; the third one asserts that it should not have specificity in mathematics curriculum in rural schools; and, at last, the fourth one proposing that the schools should also offer technical training for rural jobs